Back to normal? Strategies in gender equality for a new and healthy coexistence in Peru - Bustillos, Diego (2022)
Women have historically been part of the conception and transformation of society. They have contributed from various fields, whether as activists, leaders, professionals or heads of household. Despite this, in the current reality, many are expropriated from their lives, their bodies and their life projects. An example of this are the consequences of the health crisis generated by covid-19; which, in addition to generating human and economic losses in Peru, have exposed the capitalist and patriarchal society that we are. Undoubtedly, this pandemic represents numerous challenges and contradictions that are difficult to resolve, since it shows the urgency of the structural transformations that, although they are very complex, short and medium-term measures must be considered to provide solutions in the home and of the State. Precisely, this work is part of the sustained concern regarding the new coexistence that will be established once the pandemic generated by covid-19 is over. Problematize the “new normal”, in light of what it would mean to return to the “old normal”, which is characterized by deep gender inequalities. Therefore, the purpose of this work will be to reflect on the need to integrate the gender variable in public policies and in relationships in daily life in order to face this new situation. The methodology used has been a bibliographic review. Likewise, it will be necessary to analyze the figures from institutions that show that gender inequalities have intensified during the pandemic. Five categories will be analyzed: concept of care, violence against women, masculinities, comprehensive sexual education and new coexistence. It is concluded that, despite the fact that gender inequality and domestic violence increased drastically during the contingency, this crisis should be an opportunity to work, through strategies from civil society and public policies, in pursuit of achieving a new normality free of all violence, fair and with equality.